Neodymium-iron-boron permanent magnet as well as composite anticorrosive coating, preparation method and application thereof

By using a composite anticorrosion coating combined with polydimethylsiloxane and nanocomponents on the NdFeB permanent magnet, the problem of poor corrosion resistance of NdFeB permanent magnet is solved, and higher corrosion resistance and longer service life are achieved, while reducing production costs and solving environmental protection problems.

CN119626698APending Publication Date: 2025-03-14TIANJIN SANHUAN LUCKY NEW MATERIAL CO LTD +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411203414.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-29
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

Due to its poor corrosion resistance, neodymium iron boron permanent magnets are prone to rust and corrosion, resulting in shortening their service life. In addition, traditional anti-corrosion processes have problems with low binding force, high cost and environmental protection.

Method used

A composite anticorrosion coating combining polydimethylsiloxane and nanocomponents is used to improve the density and toughness of the coating through the skeleton support of the nanocomponents and the adhesion of polydimethylsiloxane, thereby enhancing the anticorrosion performance.

Benefits of technology

It significantly improves the corrosion resistance of neodymium iron boron permanent magnets, extends its service life, reduces production costs, and solves environmental protection problems in traditional processes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119626698A_ABST
    Figure CN119626698A_ABST
Patent Text Reader

Abstract

The invention provides a neodymium-iron-boron permanent magnet and a composite anti-corrosion coating, a preparation method and application thereof, the composite anti-corrosion coating comprises polydimethylsiloxane, a curing agent and a nano component, the anti-corrosion coating has higher resistivity and better insulativity, has excellent mechanical property and anti-corrosion performance, and can be applied to the field of permanent magnets. Batch spraying can be realized by adopting a high-pressure spraying method, and the method is suitable for industrial production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of NdFeB permanent magnet anticorrosion, and in particular to a NdFeB permanent magnet and a composite anticorrosion coating, a preparation method and use thereof. Background Art

[0002] Sintered NdFeB permanent magnets have been widely used in high-tech fields such as wind power generation, aerospace, communications, transportation, home appliances and intelligent manufacturing due to their excellent comprehensive magnetic properties. However, NdFeB permanent magnets are mainly composed of NdFeB main phase, Nd-rich phase and Boron-rich phase, which makes NdFeB permanent magnets have the disadvantage of poor corrosion resistance, which seriously affects their use. Moreover, because the surface of NdFeB permanent magnets is loose and porous and contains highly active Nd-rich phases, NdFeB permanent magnets are very easy to rust and corrode, so surface anti-corrosion treatment is required.

[0003] For the corrosion protection of NdFeB permanent magnets, traditional processes include electroplating copper-nickel, chemical plating, electroplating zinc, phosphating, electrophoresis and other methods, but the above methods have certain defects. If the electroplating copper-nickel in the above method is adopted, the nickel-copper-nickel coating solution system prepared by this method is an acidic system. During the electroplating process, it is easy to cause micro-corrosion to the NdFeB substrate to form a loose layer, which reduces the bonding force between the coating and the substrate. In addition, the electroplating layer has a honeycomb structure with low density, which affects the corrosion resistance of the coating to a certain extent. In recent years, the development of spray anti-corrosion technology has been rapid. Its epoxy resin has the advantages of hydrophilicity and low permeability, excellent waterproofness, chemical corrosion resistance, and insulation properties, but there are disadvantages of low bonding between the coating and the substrate and low utilization rate of epoxy paint, which further increases the manufacturing cost. In the later stage, the epoxy paint needs to be treated for environmental protection, and environmental protection issues are prominent.

[0004] Furthermore, as the application scope of NdFeB magnets continues to expand and the environment in which they are used becomes increasingly harsh, the requirements for surface protective coatings are also becoming higher and higher. For example, magnets used in offshore wind power generation have very high corrosion resistance requirements, and magnets used in hybrid power generation are in alternating hot and cold environments for a long time, so the requirements for the coating to be resistant to high temperature, moisture and heat are very high.

[0005] Therefore, it is urgent to develop new surface corrosion protection processes and products for NdFeB permanent magnets. Summary of the invention

[0006] In order to solve the above technical problems, the present invention provides a NdFeB permanent magnet and its composite anti-corrosion coating, preparation method and use. By combining polydimethylsiloxane and nano components, the corrosion resistance of the NdFeB permanent magnet can be effectively improved, the use environment of the NdFeB permanent magnet can be expanded, and its service life can be extended, and its application prospect is broad.

[0007] To achieve this object, the present invention adopts the following technical solutions:

[0008] In a first aspect, the present invention provides a composite anti-corrosion coating for a NdFeB permanent magnet, wherein the composite anti-corrosion coating comprises polydimethylsiloxane, a curing agent and nano-components.

[0009] Compared with the traditional surface treatment methods such as copper-nickel plating, zinc plating, and electrophoresis, the composite anti-corrosion coating of the NdFeB permanent magnet provided by the present invention has a significantly improved anti-corrosion performance of the polydimethylsiloxane coating doped with nanomaterials, the coating has impact toughness, and the production cost is significantly reduced. The nano-component has the function of skeleton support and mechanical toughness adjustment, while the polydimethylsiloxane can flow and has the function of adhesion. During the curing process, the polydimethylsiloxane is fully filled, adhered and cured in the skeleton built by the nano-component, and the two play a synergistic role, thereby increasing the density and toughness of the coating structure, improving the corrosion resistance and mechanical strength of the anti-corrosion coating, and effectively isolating the corrosive medium.

[0010] Preferably, the mass content of nano components in the composite anti-corrosion coating is 0.5-9wt%, for example, it can be 0.5wt%, 1.5wt%, 2.4wt%, 3.4wt%, 4.3wt%, 5.3wt%, 6.2wt%, 7.2wt%, 8.1wt% or 9wt%.

[0011] The polydimethylsiloxane coating doped with nano-components in the present invention has the advantage of better insulation. Since the carbon nanotubes in the nano-components are conductive materials, a high doping amount will lead to poor insulation of the polydimethylsiloxane coating, thereby affecting the insulation performance of the coating.

[0012] Preferably, the mass ratio of the polydimethylsiloxane to the curing agent is (8-12):1, for example, it can be 8:1, 8.5:1, 8.9:1, 9.4:1, 9.8:1, 10.3:1, 10.7:1, 11.2:1, 11.6:1 or 12:1.

[0013] Preferably, the nanocomponents include any one of silicon dioxide, zirconium dioxide or carbon nanotubes or a combination of at least two of them, wherein typical but non-limiting combinations are a combination of silicon dioxide and zirconium dioxide, a combination of carbon nanotubes and zirconium dioxide, a combination of silicon dioxide and carbon nanotubes, and a combination of carbon nanotubes, silicon dioxide and zirconium dioxide.

[0014] Preferably, the molecular weight of the polydimethylsiloxane is in the range of 4500 to 7000, for example, 4500, 5000, 5500, 6000, 6500 or 7000.

[0015] Preferably, the size of the nano-component is 1 to 300 nm, for example, it can be 1 nm, 35 nm, 50 nm, 68 nm, 101 nm, 134 nm, 168 nm, 201 nm, 234 nm, 267 nm or 300 nm.

[0016] The size of the nano-component in the present invention is preferably controlled within the range of 1 to 300 nm. When the size of the nano-component is less than 1 nm, the nano-material is easily agglomerated, which affects its skeleton support function in the coating and reduces the mechanical toughness of the coating. When the size is greater than 300 nm, it cannot be effectively dispersed during the preparation process, resulting in the inability of the nano-material to be evenly dispersed in the polydimethylsiloxane.

[0017] Preferably, when the nanocomponent is a ceramic material, the size is 50 to 300 nm; when the nanocomponent is a single-walled carbon nanotube, the outer diameter is 1 to 2 nm, for example, it can be 1 nm, 1.1 nm, 1.2 nm, 1.3 nm, 1.4 nm, 1.5 nm, 1.8 nm, 1.9 nm or 2.0 nm; when the nanocomponent is a multi-walled carbon nanotube, the size is 1 to 100 nm.

[0018] Preferably, the curing agent includes a photocuring component and / or a thermal curing component.

[0019] Preferably, the photocurable component includes any one of pentaerythritol triacrylate, benzoin dimethyl ether, 2,4,6-trimethylbenzoyl-diphenylphosphine oxide or 2-hydroxy-2-methyl-phenylacetone-1, or a combination of at least two thereof.

[0020] Preferably, the thermal curing component includes any one of Sylgard 184, butyl diphenylcarbamate, diisopropylbenzene peroxide or ethoxylated trimethylolpropane triacrylate, or a combination of at least two thereof, wherein typical but non-limiting combinations are a combination of Sylgard 184 and butyl diphenylcarbamate, a combination of butyl diphenylcarbamate and butyl diphenylcarbamate, a combination of Sylgard 184 and butyl diphenylcarbamate, and a combination of diisopropylbenzene peroxide and butyl diphenylcarbamate.

[0021] Preferably, the thickness of the composite anti-corrosion coating is 3 to 30 μm, for example, it may be 3 μm, 6 μm, 9 μm, 12 μm, 15 μm, 18 μm, 21 μm, 24 μm, 27 μm or 30 μm.

[0022] In the present invention, when the film thickness is less than 3 microns, the corrosion resistance requirement cannot be met; when the film thickness is greater than 30 microns, the larger film thickness affects the mechanical toughness of the film, and the surface is prone to cracks under the impact of the external environment, reducing the bonding force between the film and the magnet, affecting the corrosion resistance of the magnet; on the other hand, it exceeds the size limit of the magnet, affecting the assembly of the magnet.

[0023] In a second aspect, the present invention provides a method for preparing the composite anti-corrosion coating of the NdFeB permanent magnet according to the first aspect, the preparation method comprising the following steps:

[0024] The polydimethylsiloxane, the curing agent and the nano-component are mixed in a solvent to obtain a dispersion system.

[0025] The dispersed system is coated on the surface of the NdFeB permanent magnet and cured to obtain the composite anti-corrosion coating of the NdFeB permanent magnet.

[0026] The preparation method of the present invention can better prepare the composite anti-corrosion coating of the NdFeB permanent magnet described in the first aspect, with uniform distribution of nano-components and excellent coating performance.

[0027] Preferably, the solvent comprises any one of ethanol, n-hexane or acetone or a combination of at least two thereof, wherein typical but non-limiting combinations are a combination of ethanol and n-hexane, a combination of acetone and n-hexane, and a combination of ethanol and acetone.

[0028] Preferably, the mixing includes: first mixing the nano-components with the solvent to obtain a first system, second mixing the polydimethylsiloxane, the curing agent and the solvent to obtain a second system, and third mixing the first system and the second system and heating to obtain a dispersed system.

[0029] The present invention further preferably performs mixing in steps, wherein both the nano-components and the polydimethylsiloxane need to be effectively dispersed to form an excellent film layer. The step-by-step mixing can avoid the agglomeration of the nano-components and the polydimethylsiloxane, thereby effectively improving the mechanical properties of the film, and the magnetic properties of the magnet will not be affected by the agglomeration of the nano-components.

[0030] Preferably, the first mixing is performed under ultrasonic and / or magnetic stirring conditions.

[0031] Preferably, the first mixing comprises magnetic stirring and ultrasound performed sequentially.

[0032] Preferably, the duration of magnetic stirring in the first mixing is 10 to 30 min, for example, 10 min, 13 min, 15 min, 17 min, 19 min, 22 min, 24 min, 26 min, 28 min or 30 min.

[0033] Preferably, the speed of magnetic stirring in the first mixing is 150-300 rad / min, for example, it can be 150 rad / min, 160 rad / min, 170 rad / min, 180 rad / min, 200 rad / min, 230 rad / min, 240 rad / min, 250 rad / min, 280 rad / min or 300 rad / min, etc.

[0034] Preferably, the duration of ultrasound in the first mixing is 5 to 15 min, for example, 5 min, 7 min, 8 min, 9 min, 10 min, 11 min, 12 min, 13 min, 14 min or 15 min.

[0035] Preferably, the frequency of ultrasound in the first mixing is 25-60 KHz, for example, 25 KHz, 26 KHz, 30 KHz, 32 KHz, 35 KHz, 40 KHz, 45 KHz, 50 KHz, 55 KHz or 60 KHz.

[0036] Preferably, the content of nanocomponents in the first system is 3-15wt%, for example, it can be 3wt%, 3.5wt%, 4wt%, 4.5wt%, 5wt%, 5.5wt%, 6wt%, 6.5wt%, 7wt%, 8wt%, 9wt%, 10wt%, 11wt%, 12wt%, 13wt%, 14wt% or 15wt%, etc.

[0037] Preferably, the second mixing is performed under ultrasonic and / or magnetic stirring conditions.

[0038] Preferably, the duration of magnetic stirring in the second mixing is 3 to 6 h, for example, 3 h, 3.4 h, 3.7 h, 4 h, 4.4 h, 4.7 h, 5 h, 5.4 h, 5.7 h or 6 h.

[0039] Preferably, the speed of magnetic stirring in the second mixing is 200-300 rad / min, for example, it can be 200 rad / min, 210 rad / min, 220 rad / min, 230 rad / min, 240 rad / min, 250 rad / min, 260 rad / min, 270 rad / min, 280 rad / min, 290 rad / min or 300 rad / min, etc.

[0040] Preferably, the content of polydimethylsiloxane in the second system is 10-30wt%, for example, it can be 10wt%, 13wt%, 15wt%, 17wt%, 19wt%, 22wt%, 24wt%, 26wt%, 28wt% or 30wt%.

[0041] Preferably, the third mixing is performed under ultrasonic and / or magnetic stirring conditions.

[0042] Preferably, the duration of magnetic stirring in the third mixing is 3 to 6 h, for example, 3 h, 3.4 h, 3.7 h, 4 h, 4.4 h, 4.7 h, 5 h, 5.4 h, 5.7 h or 6 h.

[0043] Preferably, the speed of magnetic stirring in the third mixing is 200-300 rad / min, for example, it can be 200 rad / min, 210 rad / min, 220 rad / min, 230 rad / min, 240 rad / min, 250 rad / min, 260 rad / min, 270 rad / min, 280 rad / min, 290 rad / min or 300 rad / min, etc.

[0044] Preferably, the volume ratio of the first system to the second system in the third mixture is 1:(3-9), for example, it can be 1:3, 1:3.2, 1:3.5, 1:3.8, 1:4.0, 1:4.2, 1:4.5, 1:4.8, 1:5.0, 1:5.2, 1:6, 1:7, 1:8 or 1:9, etc.

[0045] The purpose of diluting the polydimethylsiloxane solution into n-ethane or acetone in the present invention is to make the nanomaterial to be added uniformly dispersed in the polydimethylsiloxane. Within the range of 1: (3-9), as the amount of organic solvent used increases, the dispersion performance of the nanomaterial becomes better, but it does not increase in a continuous proportional manner. When it exceeds 1: 9, the dispersibility will not be improved any more, and increasing the volume ratio will waste acetone or n-ethane and increase production costs. When the ratio of the two is less than 1: 3, the nanomaterial cannot be uniformly mixed into the polydimethylsiloxane solution, which will cause a large proportion of large agglomerates to appear, affecting the uniformity and overall performance of the film layer.

[0046] Preferably, the heating temperature is 30-50°C, for example, it can be 30°C, 33°C, 35°C, 37°C, 39°C, 42°C, 44°C, 46°C, 48°C or 50°C.

[0047] Preferably, the viscosity of the dispersion system is 130-152 Pa·s, for example, 130 Pa·s, 132 Pa·s, 135 Pa·s, 140 Pa·s, 145 Pa·s, 148 Pa·s, 150 Pa·s, 151 Pa·s or 152 Pa·s.

[0048] Preferably, the curing includes light curing and / or heat curing.

[0049] Preferably, the thermal curing temperature is 60-120°C, for example, it can be 60°C, 67°C, 74°C, 80°C, 87°C, 94°C, 100°C, 107°C, 114°C or 120°C.

[0050] Preferably, the thermal curing time is 15 to 40 min, for example, 15 min, 18 min, 21 min, 24 min, 27 min, 29 min, 32 min, 35 min, 38 min or 40 min.

[0051] In the present invention, the temperature and time of thermal curing are preferably controlled within the above range, which can better complete the curing of the film layer and avoid the viscosity of the cured film layer, and the performance of the final product is better.

[0052] Preferably, the light source for photocuring includes any one of a point light source, a line light source or a surface light source, or a combination of at least two of them, wherein typical but non-limiting combinations are a combination of a point light source and a line light source, a combination of a surface light source and a line light source, and a combination of a point light source and a surface light source.

[0053] Preferably, the ultraviolet light irradiation time of the photocuring is 1 to 100 s, for example, it can be 1 s, 12 s, 23 s, 34 s, 45 s, 56 s, 67 s, 78 s, 89 s or 100 s.

[0054] Preferably, the coating comprises spray coating and / or spin coating.

[0055] Preferably, the gas used for spraying includes air and / or nitrogen.

[0056] Preferably, the angle range of the spray gun during the spraying is 15° to 60°, for example, it can be 15°, 20°, 25°, 30°, 35°, 40°, 45°, 50°, 55° or 60°, etc., preferably 15 to 35°.

[0057] In the present invention, the angle range of the spray gun is preferably 15 to 60 degrees, which can better ensure that the desired film thickness is obtained.

[0058] Preferably, the spraying distance is 20 to 40 cm, for example, it may be 20 cm, 23 cm, 25 cm, 27 cm, 29 cm, 32 cm, 34 cm, 36 cm, 38 cm or 40 cm.

[0059] Preferably, the spraying pressure is 90-140 psi, for example, it may be 90 psi, 96 psi, 102 psi, 107 psi, 113 psi, 118 psi, 124 psi, 129 psi, 135 psi or 140 psi.

[0060] The present invention further preferably sets the pressure of the spray gun within the above range, which can ensure effective spraying of the paint and uniform coating during the spraying process on the one hand; on the other hand, it can avoid overspray, ensure uniform thickness of the final coating, and avoid waste of paint.

[0061] Preferably, the preparation method further comprises, before spraying: sequentially degreasing, pickling and drying the surface of the NdFeB permanent magnet.

[0062] The present invention has no special limitation on the drying in the above process. Any drying device and method known to those skilled in the art can be used, and can also be adjusted according to the actual process, for example, it can be air drying, vacuum drying or oven drying, or a combination of different methods.

[0063] Preferably, the degreasing agent used in the degreasing treatment includes any one of sodium hydroxide solution, sodium carbonate solution, sodium bicarbonate solution or potassium hydroxide solution, or a combination of at least two of them, wherein typical but non-limiting combinations are a combination of sodium hydroxide solution and sodium carbonate solution, a combination of sodium hydroxide solution and potassium hydroxide solution, and a combination of sodium hydroxide solution and sodium bicarbonate solution.

[0064] Preferably, the pickling acid comprises nitric acid.

[0065] Preferably, the pickling time is 30 to 100 s, for example, it can be 30 s, 38 s, 46 s, 54 s, 62 s, 69 s, 77 s, 85 s, 93 s or 100 s.

[0066] Preferably, the drying temperature is 80-120°C, for example, it can be 80°C, 85°C, 89°C, 94°C, 98°C, 103°C, 107°C, 112°C, 116°C or 120°C.

[0067] In a third aspect, the present invention provides a NdFeB permanent magnet, comprising the composite anti-corrosion coating of the NdFeB permanent magnet described in the first aspect, and / or a composite anti-corrosion coating prepared by the preparation method of the composite anti-corrosion coating of the NdFeB permanent magnet described in the second aspect.

[0068] In a fourth aspect, the present invention provides a use of the NdFeB permanent magnet described in the third aspect, wherein the NdFeB permanent magnet is used in the fields of wind power generation, aerospace, communications, transportation, home appliances or intelligent manufacturing.

[0069] Compared with the prior art, the present invention has at least the following beneficial effects:

[0070] (1) The composite anti-corrosion coating of the NdFeB permanent magnet provided by the present invention has excellent anti-corrosion performance, can effectively improve the corrosion resistance of the NdFeB permanent magnet, expand the use environment of the NdFeB permanent magnet, and extend its service life;

[0071] (2) Compared with the traditional electroplating copper-nickel, chemical nickel, phosphating and electrophoresis technologies, the preparation method of the composite anti-corrosion coating of the NdFeB permanent magnet provided by the present invention is more environmentally friendly and completely solves the pollution problem of the water environment caused by phosphating and other technologies;

[0072] (3) The nano-components in the composite anti-corrosion coating of the NdFeB permanent magnet provided by the present invention fully play the role of skeleton support and are evenly distributed in the coating, effectively improving the problem of poor toughness of the simple polydimethylsiloxane coating and avoiding the situation that the simple polydimethylsiloxane coating is easy to crack when subjected to mechanical impact;

[0073] (4) The preparation method of the composite anti-corrosion coating provided by the present invention does not require chamfering treatment in the early stage of the NdFeB permanent magnet, which saves the cost of the C-angle and R-angle chamfering process, can effectively shorten the production process, and increase the production efficiency of the product. BRIEF DESCRIPTION OF THE DRAWINGS

[0074] Figure 1 It is a schematic flow chart of the method for preparing the composite anti-corrosion coating provided in Example 1 of the present invention.

[0075] Figure 2 This is a microscope image of the dispersed system provided in Example 2 of the present invention at 10 times magnification. DETAILED DESCRIPTION

[0076] For the convenience of understanding the present invention, the present invention lists the following embodiments. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0077] It should be understood that, in the description of the present invention, the terms "first", "second", etc. are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Thus, a feature defined as "first", "second", etc. may explicitly or implicitly include one or more of the features. In the description of the present invention, unless otherwise specified, "plurality" means two or more.

[0078] Example 1

[0079] This embodiment provides a composite anti-corrosion coating for NdFeB permanent magnets. The flow chart of the preparation method of the composite anti-corrosion coating is shown in Figure 1 , specifically including:

[0080] Pretreatment: Place the NdFeB permanent magnet workpiece (brand N40M, specification 10*10*0.75mm) in a 15wt% sodium hydroxide degreasing solution for ultrasonic degreasing for 20 minutes, then place the workpiece in 5wt% dilute nitric acid for pickling for 60 seconds, and ultrasonically clean it 3 times. Place the cleaned NdFeB permanent magnet in an electric blast drying oven for drying, the drying time is 20 minutes, and the drying temperature is 80℃.

[0081] Preparation of dispersion system: Weigh carbon nanotube nanomaterial (single-walled carbon nanotube, outer diameter of 1.5 nm) and add it to anhydrous ethanol, stir for 10 minutes and ultrasonicate at 45KHz for 10 minutes to obtain the first system, the content of carbon nanotube nanomaterial in the first system is 13.6wt%. Weigh polydimethylsiloxane (molecular weight of 5000) and curing agent (Sylgard184), mix them in a mass ratio of 10:1, stir for 5 minutes, add them to n-ethane and stir for 3 hours to obtain the second system, the content of polydimethylsiloxane in the second system is 13wt%. Mix the first system and the second system in a volume ratio of 1:5 and stir for 3 hours at 40°C to obtain a polydimethylsiloxane solution doped with silica nanomaterial, i.e., a dispersion system.

[0082] Spraying and curing: Use spraying to evenly apply the above-prepared dispersion system to the surface of the NdFeB permanent magnet. Fill the dispersion system into the spray gun, and the solution viscosity is 143Pa·s. The technical parameters of the spraying equipment are set as the spray gun angle of 25°, the spraying distance of 20cm, the gas used by the spray gun is nitrogen, and the gas pressure is 120psi. After spraying, thermal curing is carried out at a temperature of 120°C and a curing time of 30min. After the above operation is completed, turn over the NdFeB permanent magnet and repeat the above steps to prepare a composite anti-corrosion coating, and finally obtain a NdFeB permanent magnet with a composite anti-corrosion coating. The mass content of nanocomponents in the composite anti-corrosion coating is 2.9wt%, and the thickness of the coating is 20μm.

[0083] Example 2

[0084] This embodiment provides a composite anti-corrosion coating for a NdFeB permanent magnet. The preparation method of the composite anti-corrosion coating includes:

[0085] Pretreatment: Place the NdFeB permanent magnet workpiece (brand G48EH, specification 10*10*2mm) in a 20wt% sodium carbonate degreasing solution for ultrasonic degreasing for 25 minutes, then place the workpiece in 3wt% dilute nitric acid for pickling for 100 seconds, and ultrasonically clean it 3 times. Place the cleaned NdFeB permanent magnet in an electric blast drying oven for drying, the drying time is 10 minutes, and the drying temperature is 120℃.

[0086] Preparation of the dispersion system: Weigh nano-silicon dioxide (D50 is 100 nm) and add it to anhydrous ethanol, stir for 30 minutes and ultrasonicate at a frequency of 35KHz for 15 minutes to obtain the first system, in which the content of carbon nanotube nanomaterials is 10.8wt%. Weigh polydimethylsiloxane (molecular weight is 4500) and curing agent (Sylgard184), mix the two in a mass ratio of 9:1, stir for 10 minutes, add to a mixed solvent of n-ethane and acetone (the volume ratio of n-ethane and acetone is 2:1) and stir for 6 hours to obtain the second system, in which the content of polydimethylsiloxane is 20wt%. Mix the first system and the second system in a volume ratio of 1:9 and stir for 5 hours at 40°C to obtain a polydimethylsiloxane solution doped with silica nanomaterials, i.e., a dispersion system. See the enlarged view of the dispersion system for details. Figure 2 ,from Figure 2 It can be seen that the nanomaterials are uniformly dispersed in the dispersion system provided by the present invention, and the dispersion is uniform and no agglomeration occurs.

[0087] Spraying and curing: Use spraying to evenly apply the above-prepared dispersion system to the surface of the NdFeB permanent magnet. Fill the dispersion system into the spray gun, and the solution viscosity is 138Pa·s. The technical parameters of the spraying equipment are set as the spray gun angle of 35°, the spraying distance of 40cm, the gas used by the spray gun is nitrogen, and the gas pressure is 140psi. After spraying, thermal curing is carried out at a temperature of 80°C and a curing time of 40min. After the above operation is completed, turn over the NdFeB permanent magnet and repeat the above steps to prepare a composite anti-corrosion coating, and finally obtain a NdFeB permanent magnet with a composite anti-corrosion coating. The mass content of nanocomponents in the composite anti-corrosion coating is 1.5wt%, and the thickness of the coating is 10μm.

[0088] Example 3

[0089] This embodiment provides a composite anti-corrosion coating for a NdFeB permanent magnet. The preparation method of the composite anti-corrosion coating includes:

[0090] The pre-treatment steps are the same as those in Example 1.

[0091] Preparation of dispersion system: Weigh nano-silicon dioxide (D50 is 60nm) and add it to anhydrous ethanol, stir for 30min and ultrasonicate at 60KHz frequency for 1min to obtain the first system, in which the content of carbon nanotube nanomaterial is 5wt%. Weigh polydimethylsiloxane (molecular weight is 6500) and photoinitiator (pentaerythritol triacrylate), mix them in a mass ratio of 8:1, stir for 4min, add them to n-ethane and stir for 5.5h to obtain the second system, in which the content of polydimethylsiloxane is 28wt%. Mix the first system and the second system in a volume ratio of 1:3 at 50°C and stir for 4.5h to obtain a polydimethylsiloxane solution doped with silicon dioxide nanomaterial, i.e., a dispersion system.

[0092] Spraying and curing: Use spraying to evenly coat the prepared dispersion system onto the surface of the NdFeB permanent magnet. Fill the dispersion system into the spray gun, and the solution viscosity is 140Pa·s. The technical parameters of the spraying equipment are set as follows: the angle of the spray gun is 20°, the spraying distance is 35cm, the gas used by the spray gun is nitrogen, and the gas pressure is 100psi. After spraying, UV curing is performed, the curing time is 20s, and the light source is a point light source. After the above operation is completed, turn over the NdFeB permanent magnet and repeat the above steps to prepare a composite anti-corrosion coating, and finally obtain a NdFeB permanent magnet with a composite anti-corrosion coating. The mass content of nanocomponents in the composite anti-corrosion coating is 0.8wt%, and the thickness of the coating is 5μm.

[0093] Example 4

[0094] This embodiment provides a composite anti-corrosion coating for NdFeB permanent magnets. The composite anti-corrosion coating is the same as that of Embodiment 1 except that the mass content of carbon nanotube nanomaterial is 0.4wt%, and details thereof will not be repeated here.

[0095] Example 5

[0096] This embodiment provides a composite anti-corrosion coating for NdFeB permanent magnets. The composite anti-corrosion coating is the same as that of Embodiment 1 except that the mass content of carbon nanotube nanomaterials is 9.5wt%, and details thereof will not be repeated here.

[0097] Example 6

[0098] The present embodiment provides a composite anti-corrosion coating for NdFeB permanent magnets. The composite anti-corrosion coating is the same as Example 1 except that the carbon nanotube nanomaterial, anhydrous ethanol, polydimethylsiloxane, curing agent (Sylgard184) and n-ethane are directly mixed at one time without step-by-step mixing, and the first system and the second system are mixed and stirred at 40°C for 3 hours. The details are not repeated here.

[0099] Example 7

[0100] The present embodiment provides a composite anti-corrosion coating for NdFeB permanent magnets. The composite anti-corrosion coating is the same as that in Embodiment 1 except that the technical parameters of the spraying equipment are set such that the gas used by the spray gun is nitrogen and the gas pressure is 150 psi, and thus will not be described in detail here.

[0101] Example 8

[0102] The present embodiment provides a composite anti-corrosion coating for NdFeB permanent magnets. The composite anti-corrosion coating is the same as that in Embodiment 1 except that the technical parameters of the spraying equipment are set such that the gas used in the spray gun is nitrogen and the gas pressure is 80 psi, and thus will not be described in detail here.

[0103] Example 9

[0104] This embodiment provides a composite anti-corrosion coating for NdFeB permanent magnets. The composite anti-corrosion coating is the same as that of Embodiment 4 except that the carbon nano zirconium dioxide (D50 is 60 nm) is replaced by nano zirconium dioxide with D50 of 400 nm, and is not described again.

[0105] Comparative Example 1

[0106] This comparative example provides a NdFeB permanent magnet, which only adopts the same pretreatment steps as Example 1, and is not coated with an anti-corrosion coating.

[0107] Comparative Example 2

[0108] This comparative example provides a NdFeB permanent magnet, which is the same as Example 1 except that no carbon nanotube material is added to the NdFeB permanent magnet, and will not be described in detail here.

[0109] Test method: Salt spray test conditions: temperature 35±2℃, 50±5g / LNaCl, splash speed 1~2ml / 80cm 2 h, PH:6.5~7.2.

[0110] The PCT experimental conditions were: temperature 120±2°C, 100% RH, absolute pressure: 0.2 MPa.

[0111] The conditions of the wet heat test are: temperature 85±2°C, 2 atmospheres, and 100% humidity.

[0112] The test results of the above embodiments and comparative examples are shown in Table 1.

[0113] Table 1

[0114]

[0115] From Table 1, we can see the following points:

[0116] (1) It can be seen from Examples 1 to 3 that the composite anti-corrosion coating of the NdFeB permanent magnet provided by the present invention not only has a tensile strength of more than 5.9 MPa, but also has a salt spray test time of more than 440 h, a PCT test weathering resistance of more than 150 h, and a wet heat test weathering resistance of more than 300 h. This shows that the composite anti-corrosion coating of the NdFeB permanent magnet provided by the present invention significantly improves the anti-corrosion and heat resistance of the composite anti-corrosion coating by synergistically using polydimethylsiloxane, a curing agent and nano-components, and has excellent mechanical properties;

[0117] (2) It can be seen from the comprehensive embodiment 1 and comparative examples 1 to 2 that in comparative example 1, no anti-corrosion coating is applied, and the final salt spray test time is only 0.5h, the PCT test weathering is only 0.5h, and the wet heat test weathering is only 2h. In comparative example 2, no nano-component is added, and the final salt spray test time is only 300h, the PCT test weathering is only 120h, and the wet heat test weathering is only 220h. In addition, the tensile strength is reduced to 4.5MPa, and the mechanical properties and anti-corrosion properties are significantly reduced compared with those in embodiment 1. This shows that the present invention uses nano-components and polydimethylsiloxane in the composite anti-corrosion coating of NdFeB permanent magnets, and the anti-corrosion properties and mechanical properties are better;

[0118] (3) Combining Example 1 and Examples 4-5, it can be seen that the mass content of carbon nanotube nanomaterial in Example 1 is 2.9wt%, compared with 0.4wt% and 9.5wt% in Examples 4-5 respectively. The salt spray test time in Example 1 is 480h, the PCT test weathering is 200h, and the wet heat test weathering is 300h, while the corrosion resistance in Examples 4-5 is significantly reduced. In addition, the content of nano components in Example 4 is relatively low, resulting in a large stress of the polydimethylsiloxane film, which is easy to fall off and crack. The reduction of carbon nanotube materials will reduce the strength of the film layer, making it more easily damaged by impact. In addition, the surface roughness of the film layer in Example 4 is reduced, which causes problems when adhering glue. In Example 5, since carbon nanotubes are conductive materials, a high doping amount will cause the insulation of the polydimethylsiloxane coating to deteriorate, thereby affecting the insulation performance of the coating. This shows that the present invention preferably controls the content of nano components within a specific range, which can better improve the comprehensive performance of the composite anti-corrosion coating of the NdFeB permanent magnet.

[0119] (4) It can be seen from Example 1 and Example 6 that only one-step mixing process is used in Example 6, which results in that the nano-components and polydimethylsiloxane cannot be effectively dispersed, and a large number of agglomerates will be formed in the film layer, reducing the mechanical properties of the film. In addition, if materials such as carbon nanotubes form agglomerations in a certain area to form pathways, the insulation of the film layer will be reduced, further affecting the magnetic properties of the magnet. This shows that the present invention preferably adopts a step-by-step mixing method, which is more conducive to improving the dispersion uniformity of the nano-components and polydimethylsiloxane, and ultimately better improving the performance of the coating;

[0120] (5) It can be seen from Example 1 and Examples 7 to 8 that the present invention preferably controls the gas pressure of the spray gun within a reasonable range, which can better control the thickness of the composite anti-corrosion coating, and thus is more conducive to ensuring the anti-corrosion performance and mechanical properties of the composite anti-corrosion coating;

[0121] (6) It can be seen from Example 1 and Example 9 that the size of the nanocomponents has an impact on the agglomeration of the nanocomponents during the dispersion process. The present invention can avoid agglomeration while ensuring the uniformity of the film surface by controlling the size of the nanocomponents within a reasonable range, and can avoid the phenomenon of clogging the gun tip after large agglomerations. Finally, the anti-corrosion performance and mechanical properties of the coating in Example 1 are better.

[0122] The present invention illustrates the detailed features of the present invention through the above embodiments, but the present invention is not limited to the above detailed features, that is, it does not mean that the present invention must rely on the above detailed features to be implemented. Those skilled in the art should understand that any improvement to the present invention, equivalent replacement of the technical features selected by the present invention, addition of auxiliary technical features, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. A composite anti-corrosion coating for NdFeB permanent magnets, characterized in that: The composite anti-corrosion coating comprises polydimethylsiloxane, a curing agent and nano components.

2. The composite anti-corrosion coating according to claim 1, characterized in that: The mass content of the nano-components in the composite anti-corrosion coating is 0.5-9wt%; Preferably, the mass ratio of the polydimethylsiloxane to the curing agent is (8-12):

1.

3. The composite anti-corrosion coating according to claim 1 or 2, characterized in that: The nano-components include any one of silicon dioxide, zirconium dioxide or carbon nanotubes or a combination of at least two thereof; Preferably, the molecular weight of the polydimethylsiloxane is in the range of 4500 to 7000; Preferably, the size of the nano-component is 1 to 300 nm; Preferably, the curing agent includes a light-curing component and / or a heat-curing component; Preferably, the photocurable component comprises any one or a combination of at least two of pentaerythritol triacrylate, benzoin dimethyl ether, 2,4,6-trimethylbenzoyl-diphenylphosphine oxide or 2-hydroxy-2-methyl-phenylacetone-1; Preferably, the heat curing component comprises any one or a combination of at least two of Sylgard 184, diphenyl butyl carbamate, dicumyl peroxide or ethoxylated trimethylolpropane triacrylate; Preferably, the thickness of the composite anti-corrosion coating is 3 to 30 μm.

4. A method for preparing a composite anti-corrosion coating for a NdFeB permanent magnet according to any one of claims 1 to 3, characterized in that: The preparation method comprises the following steps: Mixing polydimethylsiloxane, a curing agent and nano-components in a solvent to obtain a dispersed system; The dispersed system is coated on the surface of the NdFeB permanent magnet and cured to obtain the composite anti-corrosion coating of the NdFeB permanent magnet.

5. The preparation method according to claim 4, characterized in that: The solvent includes any one of ethanol, n-hexane or acetone or a combination of at least two thereof; Preferably, the mixing comprises: first mixing the nano-components with the solvent to obtain a first system, second mixing the polydimethylsiloxane, the curing agent and the solvent to obtain a second system; and third mixing the first system and the second system and heating to obtain a dispersed system; Preferably, the first mixing is performed under ultrasonic and / or magnetic stirring conditions; Preferably, the first mixing comprises magnetic stirring and ultrasound performed sequentially; Preferably, the duration of magnetic stirring in the first mixing is 10 to 30 minutes; Preferably, the speed of magnetic stirring in the first mixing is 150 to 300 rad / min; Preferably, the duration of ultrasound in the first mixing is 5 to 15 minutes; Preferably, the frequency of the ultrasound in the first mixing is 25 to 60 KHz; Preferably, the content of the nano-component in the first system is 3-15wt%; Preferably, the second mixing is performed under ultrasonic and / or magnetic stirring conditions; Preferably, the duration of magnetic stirring in the second mixing is 3 to 6 hours; Preferably, the speed of magnetic stirring in the second mixing is 200 to 300 rad / min; Preferably, the content of polydimethylsiloxane in the second system is 10 to 30 wt %; Preferably, the third mixing is performed under ultrasonic and / or magnetic stirring conditions; Preferably, the duration of magnetic stirring in the third mixing is 3 to 6 hours; Preferably, the speed of magnetic stirring in the third mixing is 200-300 rad / min; Preferably, the volume ratio of the first system to the second system in the third mixing is 1:(3-9); Preferably, the heating temperature is 30-50°C; Preferably, the viscosity of the dispersed system is 130-152 Pa·s.

6. The preparation method according to claim 4 or 5, characterized in that: The curing includes light curing and / or heat curing; Preferably, the temperature of the thermal curing is 60 to 120°C; Preferably, the thermal curing time is 15 to 40 minutes; Preferably, the light source for photocuring includes any one of a point light source, a line light source or a surface light source, or a combination of at least two of them; Preferably, the ultraviolet light irradiation time of the photocuring is 1 to 100 seconds.

7. The preparation method according to any one of claims 4 to 6, characterized in that: The coating comprises spray coating and / or spin coating; Preferably, the gas used for spraying includes air and / or nitrogen; Preferably, the angle of the spray gun during the spraying is in the range of 15° to 60°, preferably 15° to 35°; Preferably, the spraying distance is 20 to 40 cm; Preferably, the spraying pressure is 90-140 psi.

8. The preparation method according to any one of claims 4 to 7, characterized in that: The preparation method further comprises, before spraying, sequentially degreasing, pickling and drying the surface of the NdFeB permanent magnet; Preferably, the degreasing agent used in the degreasing treatment includes any one of sodium hydroxide solution, sodium carbonate solution, sodium bicarbonate solution or potassium hydroxide solution, or a combination of at least two thereof; Preferably, the pickling acid comprises nitric acid; Preferably, the pickling time is 30 to 100 seconds; Preferably, the drying temperature is 80-120°C.

9. A neodymium iron boron permanent magnet, characterized in that: The NdFeB permanent magnet comprises the composite anti-corrosion coating of the NdFeB permanent magnet as claimed in any one of claims 1 to 3, and / or the composite anti-corrosion coating prepared by the preparation method of the composite anti-corrosion coating of the NdFeB permanent magnet as claimed in any one of claims 4 to 8.

10. Use of the NdFeB permanent magnet according to claim 9, characterized in that: The NdFeB permanent magnet is used in the fields of wind power generation, aerospace, communication, transportation, home appliances or intelligent manufacturing.

Citation Information

Cited By

  • Silanized surface grain boundary substituted and modified NdFeB magnet and preparation method thereof

    CN120727438A